Kemampuan Guru Penjasorkes dalam Perencanaan Pelaksanaan dan Evaluasi Pembelajaran Pada SMK Negeri Sekabupaten Purbalingga (Universitas Negeri Semarang, 2022)
Physical education teachers' ability in the learning process has an impact on education, improving the quality and quality of education so that it affects the teaching and learning process. For this reason, the problem of this research is how the ability of physical education teachers in the learning process at SMK Negeri Sekabupaten Purbalingga is. The purpose of this study was to determine the ability of physical education teachers in the physical education learning process which includes the planning, implementation, and evaluation processes at SMK Negeri Sekabupaten Purbalingga. This research is a type of qualitative research with a descriptive approach. The results of the research are the ability of teachers in the learning process which includes planning done by making syllabus and lesson plans, the process of implementing physical education learning is carried out in face-to-face meetings, and the assessment process is carried out through three aspects of affective, cognitive, and psychomotor. The conclusion of this study is that the ability of teachers in the physical education learning process which includes planning, implementation, and evaluation at SMK Negeri Sekabupaten Purbalingga is quite good.